Abnormal Thyroid Function in Patients with Mood Disorders: Prevalence and Associated Factors - วัฒนวิกย์กิจ ภาพันธ์; สันดุษฎี ปานใจ; พหลภาคย์ พงศธร; อภิสิทธิ์ภิญโญ ศิรินภา; ชัยอุดมสม กุศลาภรณ์ (Journal of the Psychiatric Association of Thailand, 2019)
Introduction : Mood disorders have high life-time prevalence and cause significant disabilities. Hypothalamic-pituitary-thyroid (HPT) axis dysfunction has been reported in patients with mood disorders, but the prevalence and its associations have yet to be established. Objectives : To study the prevalence of abnormal thyroid function and associated factors in patients with mood disorders Material and Methods : In this retrospective descriptive study,medical records of patients with mood disorders, including Major Depressive Disorder, Persistent Depressive Disorder (Dysthymia), BipolarI Disorder, Bipolar II Disorders and Cyclothymia, from January 1st, 2011 to August 31st,2016 were reviewed. Collected data included demographic data, underlying medical conditions, psychiatric diagnoses, medications, history of electroconvulsive therapy, and results of thyroid function test (TFT). Statistical analyses were performed using STATA 10.1. Results : From a total of 252 medical records,144 (57.14%) patients had complete data on TFT, and 49 (34.03%) patients had abnormal TFT;40 patients had abnormal FT3; 13 patients had abnormal TSH; and 2 patients had abnormal FT4. Factors including female gender and the use of second generation antipsychotics showed statistically significant association with abnormal TFT [adjusted OR 6.17 (95%CI2.5 - 15.23), p<0.001 and adjusted OR 2.3 (95%CI 1.06 - 5.02), p=0.036,respectively] Conclusion : About one-third of patients with mood disorders had abnormal TFT, and female gender and the use of second generation antipsychotics were associated with abnormal TFT.